2014
DOI: 10.12691/jfnr-2-4-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and its Association with Healthy Eating Index-2005 in Adolescents: Tehran Lipid and Glucose Study

Abstract: One of the major epidemiologic public health problems is worldwide metabolic syndrome (MetS). Since the relationship between diet quality and MetS among adolescents in developing countries has not been well understood, the present study aimed to evaluate the association between diet quality, as measured by Healthy Eating Index (HEI-2005) and the prevalence of MetS and its risk factors in a group of Tehranian adolescents. This crosssectional study was conducted on 706 adolescents, aged 10-19 years, within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
(43 reference statements)
1
10
0
Order By: Relevance
“…Many of the relationships between diet and CVD risk factors (including BP and lipids) identified in this study reflect those found in previous research in adolescents [ 42 , 44 , 81 , 82 ]. For instance, a variety of aspects of the DASH (Dietary Approaches to Stop Hypertension) diet were associated with lower SBP and DBP in this study: greater intake of total vegetables is associated with lower SBP, and greater intakes of whole fruit and greens and beans are related to DBP.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Many of the relationships between diet and CVD risk factors (including BP and lipids) identified in this study reflect those found in previous research in adolescents [ 42 , 44 , 81 , 82 ]. For instance, a variety of aspects of the DASH (Dietary Approaches to Stop Hypertension) diet were associated with lower SBP and DBP in this study: greater intake of total vegetables is associated with lower SBP, and greater intakes of whole fruit and greens and beans are related to DBP.…”
Section: Discussionsupporting
confidence: 87%
“…This research adds to a limited body of evidence connecting diet to both dyslipidemia and HTN at a young age. Notably, the protective effects of many aspects of diet, particularly whole plant foods, are more consistently connected to BP and blood lipids than the negative impacts of other aspects of diet [ 42 , 44 , 81 , 82 ]. However, this research reflects the potential positive impact of greater intake of whole plant foods, particularly vegetables, fruits, and legumes on CVD risk reduction at a young age, as well as the negative impact of sweetened beverages and refined carbohydrates on CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…An inverse significant association was observed between magnesium intakes and FBG concentrations (β = -0.08, 95% CI = -0.76, -0.017) (36). FBG or odds of FBG ≥ 100 mg/dL was not significantly associated with fructose intake (37), phytochemical index (38), glycemic index and glycemic load (39), or HEI-2005 (40). Higher adherence of LCD was not associated with higher odds of elevated blood glucose levels after 3.6 years follow-up in children and adolescents, aged 6-19 (41).…”
Section: Resultsmentioning
confidence: 96%
“…As shown in the past studies, prevalence of overweight and obesity is increasing in Iranian adolescents (prevalence of large waist circumference has increased from 12.2% in 1999-2001 to 51.8% in 2008-2011) [25,26]. This indicated that during nutrition transition incorrect eating habits have lead to increased energy intake more than the amount of required and thus overweight and obesity.…”
Section: Discussionmentioning
confidence: 80%